Assistance Program for Alternative Sweet Potato Processing into Flour, Crackers, and Ice Cream to Enhance Local Agricultural Value in Layeni Village, Central Maluku" - Mauliza Rahmi Mauliza Rahmi; Supriadi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
Sweet potato is a local food commodity with high carbohydrate content and considerable potential as an alternative staple food to rice. In Layeni Village, sweet potato, locally known as patatas, is widely cultivated and serves as an important source of household consumption and income. However, its utilization remains limited to direct consumption and fresh-market sales, resulting in low economic added value. This Community Service Program aimed to enhance community knowledge and skills in processing sweet potatoes into innovative value-added products to optimize local agricultural resources. The program employed observation, socialization, training, and hands-on practice methods involving local residents as participants. The results indicated an improvement in participants’ understanding of sweet potato product diversification and their ability to produce three processed products, namely sweet potato flour, sweet potato flour-based ice cream, and crackers made from sweet potato residue. These products demonstrate potential for development as local micro, small, and medium enterprises (MSMEs). Therefore, the program contributed to increasing the added value of sweet potato commodities while creating opportunities for community-based economic development through innovative products derived from local resources.